Automated Axis Alignment for a Nanomanipulator inside SEM and Its Error Optimization. (19th June 2017) - Zhou, Chao; Deng, Lu; Cheng, Long; Cao, Zhiqiang; Wang, Shuo; Tan, Min
Abstract : In the motion of probing nanostructures, repeating position and movement is frequently happing and tolerance for position error is stringent. The consistency between the axis of manipulators and image is very significant since the visual servo is the most important tool in the automated manipulation. This paper proposed an automated axis alignment method for a nanomanipulator inside the SEM by recognizing the position of a closed-loop controlling the end-effector, which can characterize the relationship of these two axes, and then the rotation matrix can be calculated accordingly. The error of this method and its transfer function are also calculated to compare the iteration method and average method. The method in this paper can accelerate the process of axis alignment to avoid the electron beam induced deposition effect on the end tips. Experiment demonstration shows that it can achieve a 0.1-degree precision in 90 seconds.